2015
DOI: 10.1002/2013wr014572
|View full text |Cite
|
Sign up to set email alerts
|

A generalized regression model of arsenic variations in the shallow groundwater of Bangladesh

Abstract: Localized studies of arsenic (As) in Bangladesh have reached disparate conclusions regarding the impact of irrigation‐induced recharge on As concentrations in shallow (≤50 m below ground level) groundwater. We construct generalized regression models (GRMs) to describe observed spatial variations in As concentrations in shallow groundwater both (i) nationally, and (ii) regionally within Holocene deposits where As concentrations in groundwater are generally high (>10 μg L−1). At these scales, the GRMs reveal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Where higher As concentrations are found in deep pumping wells in this study (e.g., Barisal and Kuakata, Figure ) residence time indicators (Figure ) and hydrochemical evidence (Figure ) indicate that they are unlikely to be associated with the vertical migration of shallow modern water but may represent zones where there have been lower rates of groundwater flushing due to local variations in permeability (Cardenas & Jiang, ; Gassiat et al, ; Hoque et al, ). Indeed, this has been observed elsewhere in the shallow BAS (Shamsudduha et al, ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Where higher As concentrations are found in deep pumping wells in this study (e.g., Barisal and Kuakata, Figure ) residence time indicators (Figure ) and hydrochemical evidence (Figure ) indicate that they are unlikely to be associated with the vertical migration of shallow modern water but may represent zones where there have been lower rates of groundwater flushing due to local variations in permeability (Cardenas & Jiang, ; Gassiat et al, ; Hoque et al, ). Indeed, this has been observed elsewhere in the shallow BAS (Shamsudduha et al, ).…”
Section: Discussionsupporting
confidence: 55%
“…Evidence from small‐scale studies (Harvey et al, ; Neumann et al, ) suggest that surface inputs of organic matter, induced by pumping, can lead to As mobilization in shallow aquifers (<100 m). More recent work by Shamsudduha et al () challenges this suggestion as a regional‐scale phenomenon and shows, using statistical models from national data sets, that groundwater irrigation serves to flush As from the shallow groundwater system and redistribute it to the surface. Elevated salinity and associated high Cl, B, and SO 4 (Figure ) are found at shallow (<100 m) to intermediate (100–200 m) depths at coastal sites and pose a potential threat to underlying fresh groundwater regionally in the coastal BAS.…”
Section: Discussionmentioning
confidence: 99%
“…8). Arsenic is thought to result from a higher proportion of argillaceous material and organic matter associated with the fine-medium sands of the Holocene alluvium, which produces reducing groundwater conditions, and within which, historic flushing of groundwater has been limited (McArthur et al 2004;Shamsudduha et al 2015). Many millions of people have developed symptoms of arsenic poisoning from use of the shallow groundwater for drinking water supply since the 1980s in this region (Ravenscroft et al 2004).…”
Section: Arsenicmentioning
confidence: 99%
“…In areas with extensive clay soils (e.g. central Bangladesh), studies have indicated that groundwater recharge is lower than where the soil is more permeable (Goel et al 1977;Shamsudduha et al 2011Shamsudduha et al , 2015.…”
Section: Rain-fed Rechargementioning
confidence: 99%
See 1 more Smart Citation